2007
DOI: 10.1016/j.fct.2007.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of herbal products and their constituents on human cytochrome P4502E1 activity

Abstract: Ethanolic extracts from fresh Echinacea purpurea and Spilanthes acmella and dried Hydrastis canadensis were examined with regard to their ability to inhibit cytochrome P4502E1 mediated oxidation of p-nitrophenol in vitro. In addition, individual constituents of these extracts, including alkylamides from E. purpurea and S. acmella, caffeic acid derivatives from E. purpurea, and several of the major alkaloids from H. canadensis, were tested for inhibition using the same assay. H. canadensis (goldenseal) was a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
0
28
0
1
Order By: Relevance
“…From a comparison of the likely bioavailable serum concentrations of the relevant alkylamides (Table 2) with the IC 50 values obtained in vitro (Table 3), the authors of both these studies concluded that clinically significant inhibition was unlikely but could not be excluded (Modarai et al 2007;Raner et al 2007). Unfortunately, when estimating in vivo drug-drug interactions from in vitro data, numerous pharmacokinetic parameters need to be considered, such as: inhibition potencies (K i ) for each active phytochemical component; percentage of the administered dose that reaches the liver enzymes as intact and unbound compound, in order to use clinically relevant concentrations in in vitro studies; intersubject variability, with regard to pharmacogenetics of metabolizing enzymes, transporters and receptors; estimates of the abundance of each metabolizing enzyme in the liver; and finally, the contribution of extrahepatic modes of clearance to the total body clearance of the active compounds (Butterweck and Derendorf 2008;Pelkonen and Turpeinen 2007;Rostami-Hodjegan and Tucker 2007).…”
Section: In Vitro and Ex Vivo Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…From a comparison of the likely bioavailable serum concentrations of the relevant alkylamides (Table 2) with the IC 50 values obtained in vitro (Table 3), the authors of both these studies concluded that clinically significant inhibition was unlikely but could not be excluded (Modarai et al 2007;Raner et al 2007). Unfortunately, when estimating in vivo drug-drug interactions from in vitro data, numerous pharmacokinetic parameters need to be considered, such as: inhibition potencies (K i ) for each active phytochemical component; percentage of the administered dose that reaches the liver enzymes as intact and unbound compound, in order to use clinically relevant concentrations in in vitro studies; intersubject variability, with regard to pharmacogenetics of metabolizing enzymes, transporters and receptors; estimates of the abundance of each metabolizing enzyme in the liver; and finally, the contribution of extrahepatic modes of clearance to the total body clearance of the active compounds (Butterweck and Derendorf 2008;Pelkonen and Turpeinen 2007;Rostami-Hodjegan and Tucker 2007).…”
Section: In Vitro and Ex Vivo Studiesmentioning
confidence: 97%
“…In another study (Raner et al 2007) the inhibitory potency of two ethanolic Echinacea extracts and three Echinacea alkylamides was assessed against CYP2E1 activity, both in human liver microsomes and with the recombinant human enzyme. Interestingly, the 95% ethanolic extract showed inhibition, whereas the extract in 33% ethanol did not.…”
Section: In Vitro and Ex Vivo Studiesmentioning
confidence: 99%
“…The akylamides, not the caffeic acids, can inhibit CYP2E1 activity in human liver microsomes and baculovirus-expressed enzymes. 45 Collectively, these data indicate that Echinacea can inhibit several CYPs, such as CYP1A2, -2C9, -2E1, -3A4, and -2D6, based on the findings from these laboratory studies, but the proportion of the constituents will likely determine the overall effect on CYP metabolism.…”
Section: Laboratory Preclinical and Animal Studiesmentioning
confidence: 81%
“…At the same time, many compounds containing terminal alkyne structure are not only important intermediates, especially for the syntheses of different 1,2,3-triazoles [23][24][25][26][27], but also have different bioactivities [28,29], and even some propargyl ester can be used as a herbicide [30]. However, there is no report on the synthesis of propargyl esters simultaneously containing the structure of 2(5H)-furanone and amino acid as the bioactive units.…”
Section: Introductionmentioning
confidence: 96%